Defining sustainability in Swedish forest policy - Bernro, Mikaela (2021)
The Forest Inquiry (Skogsutredningen, SOU 2020:73) has attempted to unite stakeholder interests and societal goals through suggested solutions for new and improved forest policies. These solutions have established certain explicit and implicit problem representations within Swedish forest management and forest policy. The aim of this study has been to investigate the problem representations in the Forest Inquiry that are related to sustainable forestry and the increased polarization in the Swedish forest debate. Apart from the problem representations, it has also been examined how the different actors are being constituted, and what the potential effects of the problem representations could be on Swedish forestry. To answer the research questions, a text analysis guided by Bacchi’s framework ‘What is the problem represented to be?’ was conducted on selected parts of the Forest Inquiry. The analysis was supplemented with media articles covering the actors’ positions, reactions, and opinions on the issues and policy proposals. The analysis resulted in three overarching problem representations: (1) an issue in defining sustainable forest management, (2) conflict and polarisation within the forest debate, and (3) the landowners’ lack of biodiversity knowledge. Through these, it has been shown that the forest sector is influential in defining sustainable forestry, and that stakeholder groups are being excluded or simplified to achieve consensus in the policy making processes. The effects on Swedish forestry risks becoming a narrow discussion and further polarisation among the stakeholders.